MICROBIAL ETIOLOGY AND ANTIBACTERIAL RESISTANCE PATTERNS OF DACRYOCYSTORHINOSTOMY CASES IN THE NORTH OF IRAN S - Nemati, Shadman; Mojtahedi, Ali; Montazeri, Sina; Alizadeh Pahlavan, Pegah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Nasolacrimal duct obstruction is an annoying medical condition in both ophthalmology and otolaryngology practices. As prophylactic antibiotic therapy decreases the rates of infections, understanding the prompt microbial spectrum of the pathogens has been revealed to be highly effective in such patients. We evaluated the microbial growth and bacterial resistance patterns of Bodkin tube samples obtained from patients who underwent dacryocystorhinostomy (DCR). Methods: A total number of 72 patients were enrolled in the study, and their Bodkin tube samples were cultured 8–12 weeks after DCR at Amir-Al Momenin University Hospital of Rasht, in the north of Iran. Results: Staphylococcus epidermidis and Aspergillus fumigatus were the most common bacterial and fungal species derived from the cultures, and 23.6% and 36.1% of the patients had neither bacterial nor fungal growth, respectively. The highest antibiotic resistance rates were toward cefazolin and cloxacillin among all the studied antibiotics. Conclusion: Majority of cases had positive bacterial or fungal growth in their samples. Considering microbial resistance, proper antibiotic selection is recommended for the patients undergoing DCR.